Respuesta :
Solution:
[tex]( \sqrt{2} + 1)(5 + \sqrt{2}) \\ = \sqrt{2} (5 + \sqrt{2} ) + 1(5 + \sqrt{2} ) \\ = 5 \sqrt{2} + 2 + 5 + \sqrt{2} \\ = 7 + 6 \sqrt{2} [/tex]
Answer:
7 + 6√2
Answer:
[tex]\huge\boxed{\sf 7 + 6\sqrt{2}}[/tex]
Step-by-step explanation:
[tex](\sqrt{2} +1)(5+\sqrt{2} )\\\\= \sqrt{2} (5+\sqrt{2} )+1(5+\sqrt{2} )\\\\= 5\sqrt{2} + (\sqrt{2})^2+5+\sqrt{2} \\\\= 5\sqrt{2} + 2 + 5 + \sqrt{2} \\\\= 2+5+\sqrt{2} + 5\sqrt{2} \\\\= 7 + \sqrt{2} (1+5)\\\\= 7 + 6\sqrt{2} \\\\\rule[225]{225}{2}[/tex]
Hope this helped!